Altered Intrinsic Brain Activities in Patients with Diabetic Retinopathy Using Amplitude of Low-frequency Fluctuation: A Resting-state fMRI Study - Qi CX (Dove Medical Press, 2020)
Chen-Xing Qi, Xin Huang, Yin Shen Eye Center, Renmin Hospital of Wuhan University, Wuhan 430060, Hubei, People’s Republic of ChinaCorrespondence: Yin ShenEye Center, Renmin Hospital of Wuhan University, No. 238, Jie Fang Road, Wu Chang District, Wuhan 430060, Hubei, People’s Republic of ChinaTel +86 13871550513Email yinshen@whu.edu.cnObjective: The current study aimed to apply the amplitude of low-frequency fluctuation (ALFF) method for investigating the spontaneous brain activity alterations and their relationships with clinical features in patients with diabetic retinopathy (DR).Patients and Methods: In total, 35 patients with DR (18 males and 17 females) and 38 healthy control (HC) subjects (18 males and 20 females) were enrolled in this study. All participants underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning, respectively. The ALFF method was used to assess the spontaneous brain activity, while the mean ALFF signal values of patients with DR and HCs were classified by the receiver operating characteristic (ROC) curve. Correlation analysis was performed to calculate the relationship between the observed mean ALFF values of the altered regions in patients with DR and their clinical features.Results: Compared with the HCs, patients with DR had significantly lower ALFF values in the left and right middle occipital gyrus (MOG). In contrast, patients with DR showed higher ALFF values in the left cerebellum (CER), left inferior temporal gyrus (ITG) and left hippocampus (Hipp). However, no relationship was observed between the mean ALFF signal values of the altered regions and clinical manifestations in the patients with DR.Conclusion: We mainly found that patients with DR showed abnormal intrinsic brain activities in the left and right MOG, left CER, left ITG and left Hipp, which might provide useful information for explaining neural mechanisms in patients with DR.Keywords: diabetic retinopathy, amplitude of low-frequency fluctuations, resting state, functional magnetic resonance imaging